Conflict Resolution after Village Head Election in Jeneponto Regency (Legal and Sociological Review) - Auliah Andika Rukman; Suardi Suardi; Imelda Yanti; Indah Ainun Mutiara; Thomy Sastra Atmaja; Elly Hasan Sadeli; Mariatul Kiptiah (Universitas of Muhammadiyah Makassar, 2023)
Background. The research problem is that there was a post-village election conflict in Batujala Village, Bontoramba District, Jeneponto Regency. The aim of the research is to analyze the conflict resolution that was carried out after the election of the village head in Jeneponto Regency. Research methods. This research uses mixed qualitative and quantitative research methods, namely mixed methods concurrent embedded, simultaneously or together but with different weights. Analysis of research data using qualitative data analysis and quantitative data. For qualitative through data reduction, data display and drawing conclusions, while for quantitative data through questionnaire verification, tabulation of questionnaire data and the percentage of questionnaire data. Research result. Conflict resolution after the village head election in Jeneponto Regency was carried out in several ways, namely dominating (emphasizing) assisted by the police, making integrative efforts (together) by summoning the two conflicting parties and compromising to get an agreement between the two conflicting parties. Post-election village head conflicts can be resolved through dominance, integrative and compromise conflict resolution.